Betrayal of the spirit : my life behind the headlines of the Hare Krishna movement - Muster, Nori J. (Nori Jean), 1956- (University of Illinois Press, 1997)
Combining behind-the-scenes views of an often besieged religious group with a personal account of the author's struggle to find meaning in it, Betrayal of the Spirit takes the reader closer than any other source so far to the reality of life in the Hare Krishna movement. Nori J. Muster, a California native, joined the International Society of Krishna Consciousness (ISKON) - the Hare Krishnas - in 1977, shortly after the death of the movement's spiritual master, Srila A.C. Bhaktivedanta Swami Prabhupada. She lived in the Krishnas' western world headquarters in Los Angeles and worked for ten years as a public relations secretary and editor of the organization's newspaper, the ISKON World Review.